An Update of Democracy's Third Wave - Marsili, M. (Political Reflection Magazine, 2020)
Almost 25 years have passed since Samuel Huntington published his seminal article Democracy´s Third Wave, further expounded in his 1991 book The Third Wave: Democratization in the Late Twentieth Century. Both interest and controversy rose in a time the world was changing and the Western idea of democracy was soon to be challenged (and shattered) in unexpected ways. Since then, the world has considerably changed and while the boundaries of politics and geopolitics are blurred by new technologies. According to Huntington, by the mid-1970s, when the Helsinki Final Act was signed, the United States began to reformulate its foreign policy, and committed itself in supporting the observance of human rights and democratization at the international level. In the Helsinki Final Act was reaffirmed the fundamental principle of refraining from the threat or use of force against the territorial integrity or political independence of any state. The catch-phrase "the third wave" has come under criticism in the light of the post-Cold War world (Diamond, 2002). Countries undergoing or having undergone a transition to democracy during a wave are subject to democratic backsliding. Political scientists and theorists believe that the third wave has crested and will soon begin to ebb, just as its predecessors did in the first and second waves (Zagorski, 2003). Does Huntington´s "third wave" theory hold on regarding the recent trends and events in world politics? In this brief article, I check if Western democracies – the US and its allies – are still committed in respecting the international principles they should be bound to, or if the democracy's third wave is over.